141k views
3 votes
(2n + 1) (n - 2) = 33

User DavidRR
by
5.9k points

2 Answers

3 votes
Distribute to get

2n + 1 + n - 2 = 33

Now simplify to get

3n -1 = 33

Now begin to get the variable by itself by adding 1 to 33 and getting rid of -1

3n = 34

Divide 34 by 3

34/3 = 1.3(repeating)
User Amin Alaee
by
7.2k points
2 votes
(2n+1)(n−2)=33


2n^(2)−3n−2=33

subtract 33 from both sides..


2n^(2)−3n−2−33

=33−33
2n2−3n−35=0

factor left side of equation...

(2n+7)(n−5)=0

set factors equal to 0...

2n+7=0 or n−5=0

n=
(-7)/(2) or n=5
User Paulo Victor
by
5.9k points